In Vitro Hepatoprotective Activity of Erythrina stricta Roxb. Against Lipopolysaccharide-Induced Cytotoxicity in Human Hepatocellular Carcinoma Cell Line (Asian Journal of Pharmaceutics (AJP), 2025)
Introduction: The use of medicinal plants is deeply rooted in traditional medicine and has significantly shaped the evolution of modern pharmaceuticals. One such plant, Erythrina stricta Roxb. belonging to the Fabaceae family, has attracted interest due to its therapeutic benefits. This research explores the hepatoprotective effects of the plant’s ethanolic and ethyl acetate fractions. Materials and Methods: This in vitro study assessed the hepatoprotective effects of E. stricta Roxb. ethanolic extract and its ethyl acetate fraction on lipopolysaccharide-induced hepatotoxicity in HepG2 cells. Cell survival was evaluated through the MTT assay. Antioxidant defense parameters, including superoxide dismutase, glutathione, and catalase, along with lipid peroxidation marker malondialdehyde (MDA), were measured. Hepatic enzyme biomarkers aspartate aminotransferase, alanine aminotransferase, and alkaline phosphatase were analyzed. Phosphorylated protein kinase C (pPKC) levels were quantified by enzyme-linked immunosorbent assay. Results: Ethanolic and Ethyl acetate fractions of E. stricta Roxb. improved HepG2 cell viability and significantly restored antioxidant enzyme levels. Ethyl acetate fraction markedly decreased MDA levels and normalized liver enzyme activities. Notably, the Ethyl acetate fraction downregulated pPKC expression, indicating anti-inflammatory activity through protein kinase C signaling modulation. Conclusion: E. stricta Roxb. exhibits hepatoprotective, antioxidant, and anti-inflammatory properties in vitro. The Ethyl acetate fraction, rich in phytochemicals, may serve as a promising natural therapeutic agent for liver diseases involving oxidative stress and inflammation.